Kosentrasi BOD, Minyak dan Lemak di Permukiman Desa Bakau Besar Laut Kec. Sungai Pinyuh Kab. Mempawah - Isna Apriani; Zairin Zain; Ria Risti Astanti (Jurnal Teknologi Lingkungan Lahan Basah, 2018)
Abstract: The settlements in RW 3 and RW 4 of Bakau Besar Laut village, Sungai Pinyuh district, covers an area adjacent to two small industries, namely a shrimp farm and copra processing with no WWTP facility, generating domestic wastes that potentially pollute local settlements and farms. This research has the purpose of identifying the BOD, Grease and Fat contents in the settlement by testing the drainage water quality in the local settlements and farms. Grab Sampling method was used to sample the water, whereas Mann Whitney method served in statistical test. Result of analysis shows that BOD concentration in each drainage has surpassed the quality standard specified in Government Regulation (PP) no. 82 of 2001, but the Oil and Fat concentration did not surpass the same regulation. Based on the results of Mann whitney statistica test, it was found that the BOD, Grease and Fat content has a radius of 700 m > 1700 m (agricultural drainage) with sig value of 0.677 > 0.05; 500 m > 1500 m (inhabitants’ drainage) with sig value of 0.936 > 0.05. Recommendations include clean water treatment (PAM/drinking water company) with intake from Bakau Besar Laut river and garbage sorting based on their characteristics (e.g. organic, anorganic and toxic and hazardous), establishing WWTP (Waste Water Treatment Plant) for shrimp farms and copra processing industries as well as establishing animal waste-based Biogas processing plants as sources for fuel and compost fertilizers that can be reutilized by the people.Abstrak: Permukiman di RW 3 dan RW 4 Desa Bakau Besar Laut,Kec. Sungai Pinyuh, merupakan kawasan yang berdekatan dengan dua industri kecil yaitu tambak udang dan pengolahan kopra yang tidak memiliki [IPAL] dengan limbah domestik yang berpotensi mencemari permukiman dan pertanian di kawasan tersebut.Riset ini bertujuan untuk mengetahui kadar BOD, Minyak dan Lemak di permukiman dengan menguji kualitas air drainase warga dan pertanian. Metode Grab Sampling digunakan untuk pengambilan sampel air dan metode Mann Whitney sebagai pengujian statistik. Hasil analisis menunjukkan bahwa Konsentrasi BOD pada masing – masing drainase telah melewati standar baku mutu PP 82 tahun 2001 sedangkan konsentrasi Minyak dan Lemak tidak melewati standar baku mutu PP 82 tahun 2001. Berdasarkan hasil uji statistik Mann whitney didapatkan kadar BOD, Minyak dan Lemak diantaranya radius 700 m > 1700 m (drainase pertanian) dengan nilai sig 0,677 > 0,05; 500 m > 1500 m (drainase warga) dengan nilai sig 0,936 > 0,05. Rekomendasi berupa pengolahan air bersih (PAM) dengan intake yang berasal dari sungai Bakau Besar Laut, melakukan pemisahan sampah sesuai dengan karakteristik limbahnya yaitu organik, anorganik dan B3, mendirikan IPAL (Instalasi Pengolahan Air Limbah) untuk industri tambak udang dan pengolahan kopra serta mendirikan pengolahan Biogas berbahan baku limbah ternak sebagai sumber bahan bakar dan pupuk kompos organik yang dapat dimanfaatkan kembali oleh masyarakat.